PENERAPAN LITERASI TEKNOLOGI UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS V PADA MATERI ORGAN-ORGAN PENCERNAAN MANUSIA - Rohmatul Hidayah (Badan Penerbit STIEPARI Press, 2022)
This study aims to increase students' creativity in the material of human digestive organs by applying technological literacy at SDN Sumur Wellut III Surabaya. This type of research is Classroom Action Research (CAR). The subjects of this research were students of class V B SDN Sumur Welut III Surabaya, totaling 22 students. This research consists of two cycles. Data collection techniques used are observation and product assessment. The data analysis technique used is qualitative and quantitative data analysis. The results of the research show that the process of applying technological literacy with product assessment of making posters using the PicsArt and Canva applications can increase students' creativity in the material of human digestive organs for class V SDN Sumur Welut III Surabaya. Based on the results of the product assessment in pre-cycle conditions, the average value obtained by students was 57.5. Then in the first cycle increased to 63.4 and the second cycle to 74.3. The number of students who reached KKM ≥ 75 in the pre-cycle were 9 students, in the first cycle there were 12 students, and in the second cycle there were 19 students. The percentage of completeness in the pre-cycle is (40.9%), the first cycle is (54.5%), the second cycle is (86.3%). So that in the second cycle it has exceeded the criteria of 80% of students who reach the KKM ≥ 75. The researcher concludes that the application of technological literacy media can increase students' creativity